Urgensi Penerapan Pasal 3 UU Tindak Pidana Korupsi terhadap Dugaan Penyalahgunaan Wewenang dalam Tata Kelola Minyak Mentah: Studi Kasus Riza Chalid (Postulat, 2026)
The management of crude oil in Indonesia is vulnerable to corruption involving abuse of authority by public officials and business actors. The case of Riza Chalid and his son, Kerry Adrianto Riza, reflects the serious impact of abuse of power in the energy sector. This study analyzes the application of Article 3 of Law No. 31 of 1999 jo. Law No. 20 of 2001 in combating corruption in the energy sector. Using a qualitative approach and normative juridical method, the study shows that the implementation of Article 3 can deter corruption perpetrators and promote more transparent and accountable governance. Corruption in this sector harms state finances and worsens public welfare, particularly through rising fuel prices